ANALISIS MAKNA DAN GAYA BAHASA PUISI “DEBU” KARYA ABDUL WACHID B.S. MENGGUNAKAN PENDEKATAN SEMIOTIKA - Kalellyna Meylawati Wijaya; Indra Permana; Ika Mustika (IKIP Siliwangi, 2021)
The background of this research was based on the intereset in reviwing the langguange style in the poem using a semiotic approach. The poem a analyzed titeld “DEBU” by Abdul Wachid B.S. The purposes of this research is; 1) knowing the use of language styles of the poem analyzed, 2) knowing the meaning and marker using a semiotic approach. 3) Describe the contents of the poem analayzed. In this research using a qualitative descriptive method, namely the method used to describe the analysis of the object research by paying anttention to researchers as a key instrument in the data collection. In addition, this research uses a semiotic approach. The subjects of this study were “DEBU” poem by Abdul Wachid B.S. The results of this research can be seen from the use of language styles in these poem using several varied language and styles ranging from allegory, antitesis, metaphors, simile, repetition, and hyperbole. In addition, the semiotics approach is used to provide signifier and signified to find out the meaning contained in the phrase. The outline the meaning contained in the poem is; lifelike in the world only temporarily there is no need to be arrogant and humans also live only bring good attitude. The poem has a romantic religious friend with a bland of beautiful phrases. The topic in this research was able to be a motivation to make a literary work of poetry.